Out of the forest, out of poverty? - Levang, P.; Dounias, E.; Sitorus, S. (2005)
That forest people intimately depend on forests for their livelihoods is widely accepted and, so it is predicted, the rapid pace of deforestation in the humid tropics will soon lead them into utter destitution or, worse, drive them into cities. Socio-economic studies recently carried out among Punan hunter-gatherers in East Kalimantan (Indonesia) somehow contradict this general belief. In remote upstream villages, where natural resources are still plentiful, families barely survive throughout the year, have very reduced monetary income, no access to education and a very high infant mortality rate. In downstream villages, where forest resources are vanishing, families have access to more cash earning opportunities, they enjoy better education and very low infant mortality. From a strict economic point of view, there is a consensus among all Punan: downstream people are generally better off; but when it comes to well-being ... opinions diverge.